Human Resource Development in the Era of Technology; Technology’s Implementation for Innovative Human Resource Development - Ince Ahmad Zarqan (Universitas Airlangga, 2017)
Rapid changes in technology have affected businesses in an uncountable way, strength of a company can be measured based on the level of technology that implemented for the sake of efficiency, it posseses that the “technovation” (technology and innovation) is one of the key for improvement of human resource. Surely, it is a single important factor for a human resource management as an organization should be able to identify an improvement of its human resources. Thus, the primary purpose of the present paper is to analyze the current effects of technology on HR processes, consider the existing literature on the topic, and discuss the advantages and efficiency. In this scenario, there is a need to clearly identify a technology for an efficient management of human resources which is able to improve skills of the employees. A number of key areas of the impacts of technology on human resource development that are discussed in order to gain an innovative human resource development.Keyword : Human Resource, Development, Technology, Improvement